Impact of Minimum Wage on Youth Employment - Thomson Sitompul (Journal of Accounting and Management Innovation, 2022)
Unlike the previous study in the minimum wage, which focused on total employment and economic sector, this paper examine its effect on one demographic variable (age) by comparing covered youth employment using cross tabulation of the status and type of job and using job status only. The aim of this study is to analyze the impact of minimum wages on youth employment in Indonesia. We analyze the impact on covered youth wemployment and total youth employment. This study contributes to the limited literature on youth employment as the impact of minimum wage in developing countries, especially in Indonesia. Using cross section distric data from the 2015 on OLS method of regression, we find that the districts/cities that have a higher district minimum wage has lower covered youth employment and total youth employment. Cross tabulation used is more representative than job status to show the impact of minimum wage on covered youth employment. Ignoring cross tabulation of the status and type of job used seriously underestimates the size of covered youth emplyoment. The impact of minimum wage on covered youth employment using cross tabulation is higher than job status used. The higher the district minimum wage, the lower the covered youth employment. Surprisingly, the minimum wages reduced covered youth employment significantly more than total employment.